KONSEP RECONNECT WITH THE QUR’AN NOUMAN ALI KHAN : Kajian Tafsir Al-Qur’an di Media Sosial - Washfi, Ilham (STAI AL-ANWAR SARANG, 2022)
Al-Qur’an ṣāliḥ li kulli zamān. That statement is proved by the existence of Islam until today. Although this statement is true and could be proved, why is there still a Muslim phenomenon that has a discrepancy relationship with the Qur’an? Neither, they should want fervently to apply the values of the Qur`an and to make it a guide in life. In this matter, Nouman Ali Khan is one of interpreters (mufasser) who is concerned about this problem. The questions of why this problem can happen and how to fix it are answered by Nouman Ali Khan in his concept. The intention of this article is to describe Nouman Ali Khan’s concept, reconnect with the Qur’an. This research is explained with the analytical descriptive method. By using Wittgenstein’s language game theory, this research concludes: 1) Reconnect with the Qur’an is a process of how to connect the human heart with the Qur’an, with the result creating a human being who lives with and acts upon Qur’an’s values (qalb salīm). 2) Reconnect with the Qur’an process engage interlacing relationships emotionally and practically (rules). The emotionally means to create trust and willingness to make Qur’an as an adviser. The practically means to learn Qur’an gradually as is taught by the messenger to the companions, starting with appreciate that Qur’an truly comes from God, and then to comprehend his contents. By that result, this research is hoped to be able to give a new method in the system of teaching and learning Qur’an.